2017
DOI: 10.1016/j.brainres.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of the axonal injury marker neurofilament light protein are not influenced by blood-brain barrier permeability

Abstract: A blood biomarker to monitor individual susceptibility to neuronal injury from cranial radiotherapy could potentially help to individualize radiation treatment and thereby reduce the incidence and severity of late effects. An important feature of such a blood biomarker is that its concentration is not confounded by varying degrees of release from the brain into the blood across the blood-brain barrier (BBB). In this study, we investigated serum neurofilament light protein (NFL) concentrations in 21-day old mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 42 publications
4
36
1
3
Order By: Relevance
“…The elevation of NfL is not specific to motor neuron degeneration, as there is evidence that the source of serum NfL also originate from cortical and spinal neuronal damages [16,18]. In a mouse model where neuronal injury was induced by cranial irradiation, increase in serum NfL was observed, independently of the blood-brain barrier permeability [20]. The CNS origin of elevated levels of NfL in CSF and in serum is further confirmed by the correlation between rising levels of serum and CSF NfL with activation of neurodegeneration in an inducible mouse model of neurodegeneration [21].…”
Section: Discussionmentioning
confidence: 98%
“…The elevation of NfL is not specific to motor neuron degeneration, as there is evidence that the source of serum NfL also originate from cortical and spinal neuronal damages [16,18]. In a mouse model where neuronal injury was induced by cranial irradiation, increase in serum NfL was observed, independently of the blood-brain barrier permeability [20]. The CNS origin of elevated levels of NfL in CSF and in serum is further confirmed by the correlation between rising levels of serum and CSF NfL with activation of neurodegeneration in an inducible mouse model of neurodegeneration [21].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, recent findings from Bowman and colleagues [23] showed an association between increased BBB permeability measured by serum/CSF albumin ratio and worse cognitive decline in older adults with MCI. However, to date, no direct comparison of BBB permeability with plasma NFL concentrations or the slope of the correlation of plasma NFL with CSF NFL in the context of neurodegeneration has been reported to examine this hypothesis closer, though a small pilot study suggests blood NFL concentration is unaffected by BBB permeability [24]. Moreover, the exact clearance pathway(s) by which NFL enters the CSF and plasma have not been well characterized in the literature, and it is possible that the CSF and plasma NFL levels might reflect separate, albeit co-occurring, underlying neural injury processes.…”
Section: Discussionmentioning
confidence: 99%
“…For the proinflammatory chemokine CCL2/MCP‐1, there was a trend towards an increase. Several studies have shown an increase in MCP1/CCL2 following cranial irradiation in young and adult rodents . In the current study, the levels of CCL2 were measured 3 months following PCI, whereas in preclinical studies the increase has been acute and transient, indicating that the time‐point in this study presumably was too late.…”
Section: Discussionmentioning
confidence: 80%